Intracochlear Perfusion of Tumor Necrosis Factor-Alpha Induces Sensorineural Hearing Loss and Synaptic Degeneration in Guinea Pigs - Katsumi, Sachiyo; Sahin, Mehmet I.; Lewis, Rebecca M.; Iyer, Janani S.; Landegger, Lukas D.; Stankovic, Konstantina M. (Frontiers in Neurology, 2020)
Tumor necrosis factor-alpha (TNF-α) is a proinflammatory cytokine that plays a prominent role in the nervous system, mediating a range of physiologic and pathologic functions. In the auditory system, elevated levels of TNF-α have been implicated in several types of sensorineural hearing loss, including sensorineural hearing loss induced by vestibular schwannoma, a potentially fatal intracranial tumor that originates from the eighth cranial nerve; however, the mechanisms underlying the tumor's deleterious effects on hearing are not well-understood. Here, we investigated the effect of acute elevations of TNF-α in the inner ear on cochlear function and morphology by perfusing the cochlea with TNF-α in vivo in guinea pigs. TNF-α perfusion did not significantly change thresholds for compound action potential (CAP) responses, which reflect cochlear nerve activity, or distortion product otoacoustic emissions, which reflect outer hair cell integrity. However, intracochlear TNF-α perfusion reduced CAP amplitudes and increased the number of inner hair cell synapses without paired post-synaptic terminals, suggesting a pattern of synaptic degeneration that resembles that observed in primary cochlear neuropathy. Additionally, etanercept, a TNF-α blocker, protected against TNF-α-induced synaptopathy when administered systemically prior to intracochlear TNF-α perfusion. Findings motivate further investigation into the harmful effects of chronically elevated intracochlear levels of TNF-α, and the potential for etanercept to counter these effects.